Cell wall and DNA damage of Staphylococcus aureus by bacteriocin BM1157. (December 2020) - Yi, Lanhua; Luo, Lingli; Chen, Jiaxin; Sun, Huimin; Wang, Xin; Yi, Yanglei; Lv, Xin
Abstract: Staphylococcus aureus is one of the most common foodborne pathogens, and it can cause food poisoning. As a promising alternative to antibiotic, bacteriocin has been widely used in food as bio-preservative. In this study, the bacteriocin BM1157 had good antibacterial activity against S. aureus according to growth curve. BM1157 treatment reduced positively charged hydrophilic group of cell surface and caused an increase of cell hydrophobicity. SEM and TEM images showed that BM1157 treatment damaged cell wall and caused nonuniform distribution of cytoplasmic materials. Results of propidium iodide (PI) uptake and lactic dehydrogenase (LDH) release indicated that BM1157 treatment damaged cell envelope integrity of S. aureus . Proteome analysis showed that 117 proteins were up-regulated and 408 proteins were down-regulated after BM1157 treatment, among which enzymes involved in peptidoglycan biosynthesis and proteins related to DNA replication and repair were included. Further, real-time quantitative PCR verified the gene down-regulation of proteins of peptidoglycan biosynthesis and DNA replication and repair of S. aureus . Moreover, agarose gel electrophoresis showed that BM1157 could bind to the DNA of S. aureus . This study suggested that BM1157 killed S. aureus by damage of cell wall and DNA. Highlights: BM1157 inhibited the growth of S. aureus and increased its surface hydrophobicity. BM1157 damaged membrane integrity of S. aureus, formed pustule-like bulges on cell surface. Biosynthesis of peptidoglycan was blocked by BM1157. BM1157 bond to DNA of S. aureus, and interfered DNA replication and repair.